Psychological effects of relational job characteristics, job crafting and work engagement among hospital nurses - Santos, Alda; Castanheira, Filipa; Chambel, Maria José (Conferência - Investigação e Intervenção em Recursos Humanos, 2018)
Relational aspects of work are being given growing attention due to a progressive and global shift towards a service economy (Parker, 2014). Grant (2007) has developed a framework according to which contact with clients and impact on client lives are considered as relational job characteristics (RJCs). The psychological effects of RJCs, according to this author comprise: the perceived social impact on the lives of clients, the perceived social worth attributed to their work and the affective commitment towards clients (Grant, 2007). The psychological effects of RJCs may be considered as work resources (Santos, Chambel, & Castanheira, 2016a) and, as such, relate positively to job crafting (Demerouti, 2014), a process through which employees craft their jobs. Previous literature has shown that job crafting is related to employees’ work engagement (Vogt, Hakanen, Brauchli, Jenny, & Bauer, 2015), a work-related well-being indicator. Nursing practice has marked relational characteristics and also nurses are the largest group of health care workers, therefore playing a crucial role in quality of care and patient safety (Aiken et al., 2012). The study of nurses’ proactively crafting their jobs, which may contribute to their work-related well-being is therefore relevant. It is also original as, to our knowledge, the relationships between the psychological effects of RJCs, job crafting and work engagement have not previously been studied among nurses. We therefore aimed to study the mediating role of job crafting in the relationships between the psychological effects of relational job characteristics (RJCs) and work engagement in a sample of hospital nurses. We expected that the psychological effects of RJCs showed positive relationships with nurses’ work engagement (H1), as well as with job crafting (H2). We also expected that job crafting demonstrated a mediating role in the relationships between the psychological effects of RJCs and work engagement (H3). Data for this cross-sectional study were collected using a questionnaire (available both online and on paper) that included the following scales: the Psychological Effects of the Relational Job Characteristics Scale, used in previous studies among this population; the Job Crafting Scale (the dimensions of Increasing structural resources, Increasing social resources and Increasing challenging demands were translated and adapted into Portuguese), and the Utrecht Work Engagement Short Questionnaire, also previously validated for this population. Participants were 202 Portuguese nurses from two public hospitals. Statistical analysis included Structural Equation Modelling. The confirmatory factor analysis of the job crafting scale demonstrated that the three-factor model showed good fit indices. The study model also indicated a good fit to the data. Results showed that our hypotheses are partially supported: perceived social worth is positively related to work engagement; perceived social impact is positively related to job crafting; and job crafting explains the relationships between perceived social impact and work engagement, as perceived social impact is positively related to job crafting which in turn is relates positively to work engagement (indirect effect). This study shows job crafting as a mechanism that explains the indirect effect of perceived social impact on work engagement. Therefore, according to our findings hospitals that create opportunities for their nurses to enhance their perceptions of the impact of their jobs and that foster their job crafting are contributing to the motivation and work well-being of their nursing workforce, which may reflect in the quality of care and patient safety.